2022
DOI: 10.1186/s12978-022-01356-3
|View full text |Cite
|
Sign up to set email alerts
|

Woman and girl-centred care for those affected by female genital mutilation: a scoping review of provider tools and guidelines

Abstract: Background A woman and girl centred, rights-based approach to health care is critical to achieving sexual and reproductive health. However, women with female genital mutilation in high-income countries have been found to receive sub-optimal care. This study examined documents guiding clinicians in health and community service settings in English-speaking high-income countries to identify approaches to ensure quality women and girl-centred care for those with or at risk of female genital mutilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 74 publications
(79 reference statements)
0
10
0
Order By: Relevance
“…A scoping review of providing tools and guidelines for the care of women affected by FGM ( 16 ) found one guideline that integrated all the dimensions of patient-centred care from the Scholl model ( 36 ). However, this guidance is not focused on maternity care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A scoping review of providing tools and guidelines for the care of women affected by FGM ( 16 ) found one guideline that integrated all the dimensions of patient-centred care from the Scholl model ( 36 ). However, this guidance is not focused on maternity care.…”
Section: Discussionmentioning
confidence: 99%
“…A scoping review by Dawson et al ( 16 ) reviewed 124 FGM-related tools and guidelines from six high-income countries and found that only 10% of those guidelines addressed the principles of woman-centred care. A lack of clear guidelines defining how woman-centred care can be achieved may negatively affect health care provision.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13]61,62 Sometimes, discrepancies between the predominant culture of the host country and the minority culture of the immigrant women led to racist behaviors, especially when dealing with issues that are strongly criticized, rejected, and even punished in the host country, such as FGM. Women with FGM in high-income countries receive suboptimal care and report poor experiences of care, 63 whereas American and European gynecologists and midwives find it challenging to care for them. 43,64 These findings indicate that much is needed to improve interactions between these women and their health care providers.…”
Section: Racismmentioning
confidence: 99%
“…They recommended that services be co-designed using a culturally competent lens and highlighted the importance of community engagement and safeguarding ( 27 ). A scoping review published by Dawson et al in 2022 ( 33 ) examined guidance and tools available to healthcare workers across six English speaking high income countries (UK, Ireland, Canada, Australia, US, New Zealand). The UK had produced the majority of publications, mostly focused upon multi-professional safeguarding.…”
Section: Introductionmentioning
confidence: 99%